UPSCALING PERMEABILITY - Septi Anggraeni; Harry Hardiman (Scientific Contributions Oil and Gas, 2002)
In reservoir simulation, the engineer needs a set of permeability values estimated on grid block which are as representative as possible of the true value. However. the sample data is limited to small scale measurement relative to the scale of reservoir simulation. Therefore. we need to upscale the permeability data measurement by averaging permeability on volumes. Prior to obtain the appropriate averaging method, an upscaling experiment was performed. The averaging method at the plug scale can be specified from the probe data and the Hassler cube data, by comparison.